PRODUKSI BAHAN KERING, KADAR NITROGEN DAN FOSFOR HIJAUAN SORGUM MANIS (Sorghum bicolor L. Moench) DENGAN APLIKASI PUPUK ORGANIK DAN FOSFAT - E. Sadana; Dwi Retno Lukiwati; Karno Karno (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
Thisstudy aims to assess the effect of a combination between organic and phosphate fertilizer on dry matter production, nitrogen and phosphorus levels of sweet sorghum forage. The design was a single factor randomized complete block design with eight treatments and three replications. Parameters weredry matter production, nitrogenand phosphorus levels. The results showed that the manure 'plus'and charcoal application at first defoliation did not significantly affect the dry matter but at the second defoliation the treatments significantly affected the dry matter production. Manure 'plus' and charcoal application showed significant effects on levels of nitrogen and phosphorus at the first and the second defoliations, so that the combination treatmentgave better results than a single fertilizer (manure fertilizer, TSP, BP and Charcoal).